Sustitución del comportamiento sedentario por actividad física ligera para mejorar los marcadores cardiometabólicos de escolares y adolescentes - Garces Navarro, William Gerardo (2022)
Establish whether the substitution of sedentary behavior for light physical activity is effective in improving cardiometabolic markers in schoolchildren and adolescents. Methods Four electronic databases were reviewed: Medline (Ovid), CENTRAL, Scopus, PubMed, from June 17 to July 1, 2021. We included RCTs in English following the PICO strategy: Population: children or adolescents; Intervention: physical activity; Comparator/control: no intervention; Result: cardiometabolic risk factors. Results 3196 articles were identified, 5 were chosen for the synthesis of results. Only one trial showed a significant difference in favor of reducing BMI when replacing sedentary behavior with light physical activity. Four studies had interventions with episodes of less than 60 min and one study did not report the duration of the episodes in its intervention. The duration of episodes was not evaluated comparatively by any study. Conclusions Light physical activity could be an effective and feasible option to reduce sedentary behavior and improve cardiometabolic health. However, more experimental evidence is needed to allow these benefits to be included in international physical activity guidelines.